2019
DOI: 10.1590/1983-21252019v32n411rc
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Dris Norms for Cactus Pear Grown Under Organic Fertilization in Semiarid Conditions

Abstract: The objective of this work was to establish DRIS norms for evaluation of nutritional status of cactos pear of the Gigante cultivar grown under organic fertilization in semiarid conditions. Cladode macro and micronutrient contents and dry matter yield of 72 plots were evaluated. The experiment was conducted in a randomized block design with three replicates, using a 4×3×2 factorial arrangement consisted of four bovine manure rates (0, 30, 60, and 90 Mg ha-1 ano-1), three spacings (1.00×0.50, 2.00×0.25, and 3.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…The high coefficients of variation are more associated with micronutrients compared to macronutrients for both for Kenworth standards, expressed by leaf nutrient contents, and for DRIS standards, expressed by bivariate relationships between nutrients, at any combination of cultivar and environment. Micronutrient contents generally have high CV values (Deus et al, 2018a) even in dual relationships, as evidenced for Mn (Silva and Carvalho, 2006;Teixeira et al, 2019). This is associated with greater interference from factors in how it moves through the soil-plant system and the high variability of micronutrient analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…The high coefficients of variation are more associated with micronutrients compared to macronutrients for both for Kenworth standards, expressed by leaf nutrient contents, and for DRIS standards, expressed by bivariate relationships between nutrients, at any combination of cultivar and environment. Micronutrient contents generally have high CV values (Deus et al, 2018a) even in dual relationships, as evidenced for Mn (Silva and Carvalho, 2006;Teixeira et al, 2019). This is associated with greater interference from factors in how it moves through the soil-plant system and the high variability of micronutrient analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior works were mainly focused on the estimation of O. ficus-indica nutrient requirements for biomass production (cladode's dry matter or fresh matter) as can be appreciated in Table 3. There are interesting differences between the Brazilian (Alves 2017;Teixeira et al 2019) and the Mexican cases (Blanco-Macías et al 2010;Valdez-Cepeda et al 2013b; and the current work). The Brazilian P sufficiency ranges are notably lower than the Mexican ones.…”
Section: Discussionmentioning
confidence: 47%
“…However, in the O. ficus-indica case, the B-LA nutrient standards were developed under the basis of relationships between 1-year-old cladode macro-nutrient concentrations and produced yearly cladode fresh matter (Blanco-Macías et al 2009, 2010. Recently, sufficiency ranges have been proposed for O. ficus-indica dry matter production by Alves (2017) and Teixeira et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the range(s) of the standard deviation of the DRIS indexes of the high-yield population (Teixeira et al, 2019), the five ranges of nutrient contents in the cladodes were defined, where deficient nutritional status: < -4/3 s; low: -4/3 s to -2/3 s; normal: -2/3 s to 2/3 s; high: 2/3 s to 4/3 s; and excessive: ≥ 4/3 s (Beaufils, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…There are limited studies that revealed the reference values for the cactus pear by the methods of nutritional diagnosis. Blanco-Macías et al (2009, 2010 adopted the Compositional Nutrient Diagnosis (CND) and Boundary Line methods to elucidate the sufficiency ranges for the crop under edaphoclimatic conditions in Mexico; Teixeira et al (2019) established the DRIS norms; the interpretive standards for nutrient content in the cladodes were determined by Alves et al (2019a, b) with the help of the methods of Mathematical Chance (ChM) and Sufficiency Range; and Donato et al (2017b) established the chemical attributes of the soil cultivated with 'Gigante' cactus pear by the Sufficiency Range and Critical Level methods by the reduced normal distribution (NCRIz) in semiarid conditions of Bahia. In this context, the objective of the present study was to employ the DRIS and BIK methods to determine the reference values for nutritional diagnosis of 'Gigante' cactus pear cultivated with organic fertilization in semiarid conditions of Bahia.…”
Section: Introductionmentioning
confidence: 99%